216k views
4 votes
Jenny thinks that the expression below is equal to x²-4. If you agree, show that she is correct. If you disagree, show that she is wrong by rewriting this expression as a polynomial in standard form.(x-2)³∕x-2

1 Answer

4 votes

Answer:

Jenny is wrong the correct answer is x²+ 4 - 4 x.

Explanation:

Given that

(x-2)³∕x-2

(x-2)³∕(x-2) =(x-2) (x-2)²∕(x-2)

(x-2)³∕(x-2) = (x-2)²

As we know that

(a-b)² = a²+b² - 2 ab

So

(x-2)² = x²+ 2² - 2 ˣ 2 ˣ x = x²+ 4 - 4 x

(x-2)² = x²+ 4 - 4 x

It means that

(x-2)³∕(x-2) = (x-2)² = x²+ 4 - 4 x

So Jenny is wrong the correct answer is x²+ 4 - 4 x.

User Karata
by
6.0k points